2021
DOI: 10.1097/md.0000000000027722
|View full text |Cite
|
Sign up to set email alerts
|

Ruxolitinib (a JAK2 inhibitor) as an emerging therapy for refractory pruritis in a patient with low-risk polycythemia vera

Abstract: Introduction: Polycythemia vera (PV) is a Philadelphia-negative myeloproliferative neoplasm (MPN) characterized by the overproduction of red blood cells. The presence of JAK2 mutation is detected in up to 99% of patients with PV. Pruritis is commonly encountered in patients with PV and is considered the most troublesome symptom. Multiple treatment modalities are used for treatment; however, their efficacy is variable. Sometimes, pruritis will not improve even by the use of combined therapies. Recently, Ruxolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Wang et al ( 30 ) reported that 5 rheumatoid arthritis patients with chronic pruritus who had not responded at all to prior anti-itch therapies, including gabapentin and prednisone, were successfully treated with oral tofacitinib. A 55-year-old male patient with polycythemia vera was completely relieved of itching after 2 months of treatment with oral ruxolitinib ( 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al ( 30 ) reported that 5 rheumatoid arthritis patients with chronic pruritus who had not responded at all to prior anti-itch therapies, including gabapentin and prednisone, were successfully treated with oral tofacitinib. A 55-year-old male patient with polycythemia vera was completely relieved of itching after 2 months of treatment with oral ruxolitinib ( 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Janus kinase and signal transducer and activator of transcription (JAK-STAT) pathway is an important signalling mechanism that regulates intracellular gene expression through cytokines and cell growth factors, such as interleukin (IL) and interferon (IFN) ( 2 ). The importance of the JAK-STAT pathway began to be elucidated through the association between gene mutations and haematological and immunological diseases, including gain-of-function mutations in JAK2 in polycythemia vera, essential thrombocytosis, and myelofibrosis, and loss-of-function mutation in STAT3 of autosomal dominant hyperimmunoglobulin E syndrome ( 3 , 4 ). It is now known that JAK-dependent cytokines play an important role in the development of a number of inflammatory and autoimmune diseases ( 2 ).…”
mentioning
confidence: 99%
“…Also, it was found that in patients with Philadelphia-negative MPN, mast cells released greater levels of pruritogenic factors like histamine, leukotrienes, and interleukin-31. It was also found that in a patient with JAK2V617F mutation, basophil count was increased, and this mutation is also known to induce cytokine hypersensitivity in cell lines [3,5].…”
Section: Case Presentation: -mentioning
confidence: 93%
“…Other PV-associated pruritus treatment options include cytoreduction, phototherapy, interferonalpha, SSRIs (e.g., paroxetine), pregabalin, and naltrexone. All were tried with different results [3,6].…”
Section: Case Presentation: -mentioning
confidence: 99%
See 1 more Smart Citation